Distinct molecular profiles in Lynch syndrome‐associated and sporadic ovarian carcinomas. Issue 11 (21st June 2013) - Niskakoski, Anni; Kaur, Sippy; Renkonen‐Sinisalo, Laura; Lassus, Heini; Järvinen, Heikki J.; Mecklin, Jukka‐Pekka; Bützow, Ralf; Peltomäki, Päivi
<x xml:space="preserve">Abstract</x> Ovarian carcinoma in Lynch syndrome (LS) is associated with unexpectedly high survival; yet, beyond DNA mismatch repair (MMR) defects, the developmental mechanisms are unknown. We used established (genetic) and new (epigenetic) classifiers of ovarian cancer to explore similarities and differences between LS‐associated and sporadic diseases. To this end, all available ovarian carcinomas (n = 20) from MMR gene mutation carriers ascertained through a nation‐wide registry and 87 sporadic ovarian carcinomas of the main histological types were molecularly profiled. LS‐ovarian carcinomas were mostly of nonserous histology (12 endometrioid, seven clear cell and one serous), diagnosed at a mean age of 45.7 years, and associated with a 10‐year survival of 87%. Among LS‐ovarian carcinomas, 19/20 (95%) were MMR‐deficient vs. 11/87 (13%) among sporadic cases (p < 0.0001). In a striking contrast to the sporadic cases, the expression of p53 was normal and KRAS/BRAF mutations absent in all LS‐ovarian carcinomas. PIK3CA mutations, suggested to be a favorable prognostic factor, occurred with a frequency of 6/20 (30%), which was comparable to sporadic tumors of endometrioid or clear cell type. Tumor suppressor genes were more frequently methylated and LINE‐1 hypomethylation less common in LS‐ovarian carcinomas compared to their sporadic counterparts. The patterns of genetic and epigenetic alterations reflected the origin as LS vs. sporadic cases on one hand and the histological type on the other hand. In conclusion, the significant molecular differences observed between LS‐associated and sporadic ovarian carcinomas help explain the different behavior of these tumors and emphasize the need for tailored clinical management.